2022
DOI: 10.1186/s13054-022-04174-y
|View full text |Cite
|
Sign up to set email alerts
|

Circulating N-formylmethionine and metabolic shift in critical illness: a multicohort metabolomics study

Abstract: Background Cell stress promotes degradation of mitochondria which release danger-associated molecular patterns that are catabolized to N-formylmethionine. We hypothesized that in critically ill adults, the response to N-formylmethionine is associated with increases in metabolomic shift-related metabolites and increases in 28-day mortality. Methods We performed metabolomics analyses on plasma from the 428-subject Correction of Vitamin D Deficiency i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…In sepsis, circulating N -formyl peptides including f-Met contribute to sepsis pathophysiology through damage-associated molecular pattern (DAMP) signaling which amplifies tissue-damaging inflammation (Harrington et al, 2017 ) and inhibits neutrophil defense against secondary nosocomial infection (Kwon et al, 2021 ). As has been described recently in two large ICU cohorts (Sigurdsson et al, 2022 ), we found that f-Met is not only increased in septic shock (Fig. 2 A), but also trended towards being positively correlated with sepsis severity (ρ = 0.29, P = 0.07; Fig.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…In sepsis, circulating N -formyl peptides including f-Met contribute to sepsis pathophysiology through damage-associated molecular pattern (DAMP) signaling which amplifies tissue-damaging inflammation (Harrington et al, 2017 ) and inhibits neutrophil defense against secondary nosocomial infection (Kwon et al, 2021 ). As has been described recently in two large ICU cohorts (Sigurdsson et al, 2022 ), we found that f-Met is not only increased in septic shock (Fig. 2 A), but also trended towards being positively correlated with sepsis severity (ρ = 0.29, P = 0.07; Fig.…”
Section: Resultssupporting
confidence: 85%
“…Consistent with studies in three large ICU cohorts (Kwon et al, 2021 , Sigurdsson et al, 2022 ) and consistent with studies of ICU molecular epidemiology that circulating levels of mitochondrial constituents (mtDNA (Johansson et al, 2018 , Wang et al, 2020 ) and N -formyl-peptides (Kwon et al, 2021 )) are associated with deleterious ICU outcomes, we found that f-Met is increased in septic shock and positively correlated with both severity and mortality. It has been generally assumed that the increased circulating f-Met in sepsis reflects mitochondrial dysfunction, but because f-Met is also produced by bacteria, its origin is not certain.…”
Section: Discussionsupporting
confidence: 86%
“…The process of methionine entering the ribosome occurs in the mitochondria of eukaryotic cells, Escherichia coli, and other bacteria [31]. Recent data from critically ill patients have shown that circulating N-formylmethionine is related to metabolic shift and high mortality which may involve impaired mitochondrial oxidation, elevated branch chain amino acid metabolism, and triggering the pentose phosphate pathway [32]. Multiple sugars are classified under the label "Hexose" including glucose, galactose, and fructose, which may suggest that high levels of sugar intake or circulating glucose contribute to gait decline.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, levels of fMet were elevated in patients with COVID-19, particularly in critically ill patients. Elevated levels of fMet were recently described in non-COVID-19 critically ill patients, associated with a metabolic shift, and heightened mortality [ 70 ], as well as in patients with other inflammatory conditions, including vasculitis, SSC, and RA, wherein fMet levels contributed to neutrophil activation [ 21 , 30 , 31 ]. However, in COVID-19 patients, levels of fMet only correlated with levels of neutrophil activation markers (calprotectin) in patients with mild-to-moderate disease, whereas for critically ill patients, no such correlations were observed.…”
Section: Discussionmentioning
confidence: 99%